2017
DOI: 10.3390/f8040135
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biochemical Properties of Soils Developed from Different Lithologies in Northwestern Spain (Galicia)

Abstract: Physical and chemical soil properties are generally correlated with the parent material, as its composition may influence the pedogenetic processes, the content of nutrients, and the element biocycling. This research studied the chemical and biochemical properties of the A horizon from soils developed on different rocks like amphibolite, serpentinite, phyllite, and granite under a relatively similar climatic regime from Galicia (northwest Spain). In particular, the effect of the parent material on soil evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have shown that soil parent material is the key to determining the differences in soil properties and mineral element composition (Cardelli et al 2017) and is related to nutrient cycling in the soil-ecosystem and its fertility (Anda et al 2015). Therefore, the soil parent material indirectly affects soil bacterial community through its physicochemical properties and mineral element composition.…”
Section: Relationship Among Soil Parent Matter Physicochemical Propementioning
confidence: 99%
“…Previous studies have shown that soil parent material is the key to determining the differences in soil properties and mineral element composition (Cardelli et al 2017) and is related to nutrient cycling in the soil-ecosystem and its fertility (Anda et al 2015). Therefore, the soil parent material indirectly affects soil bacterial community through its physicochemical properties and mineral element composition.…”
Section: Relationship Among Soil Parent Matter Physicochemical Propementioning
confidence: 99%
“…Table 2 explained that there are soils containing gravel and stones with loam to silt loam. The higher drainage portions of the gravel infused soil may move P into groundwater and nearby streams, whereas silty loam may retain more P. The primary soil order in Maine is Spodosols, susceptible to P deficiency with the third minimum distribution of P among the 12th order after Andisols and Vertisols [124]. A University of Kentucky study on P showed that testing soil P changed under different soils with the same rate of P application [123].…”
Section: Resultsmentioning
confidence: 99%
“…Avl P demonstrated significant variation at the topsoil under different land uses (p > 0.05). This infers the effect of the examined land uses on Avl P. However, in examining chemical and biochemical properties of soils developed from different lithologies in Northwestern Spain (Galicia), Cardelli et al (2017) reported low values of available P (with the exception of the soils on serpentinite and phyllite). They opined that this circumstance was ascribed to both parent rocks and environmental situations.…”
mentioning
confidence: 80%